Assessment Techniques for Aqidah Akhlak Subjects at Madrasa of Tsanawiyah - Nurmawati Nurmawati; As'ad As'ad; Diana Prasti (STAI Hubbulwathan Duri, 2023)
Evaluation of learning is not complete without an assessment. This research aimed to go deeper into the teacher assessment approach of Aqidah Akhlak in class VIII of a madrasah of tsanawiyah in Bulan-Bulan. Three questions are posed: (1) who plans teachers' judgements, (2) how teachers' judgements are put into practice each month, and (3) what variables help and hinder teachers' application of judgement to questions of aqidah ethics. A descriptive qualitative approach was used for this investigation. For this study, we used observation, interviews, and documentation. According to the findings, (1) teachers should be responsible for determining the attitude assessment objectives, the attitude assessment techniques and instruments, and the form of assessment, techniques, and instruments in class VIII aqidah morals lessons (with the exception of 9 aspects that will be assessed), and (2) the implementation of the attitude assessment is not yet optimal due to a discrepancy between the implementation. The lack of lesson repetition, the diversity of the student body, and the limited amount of time available are all variables that work against the teacher. Hence, the assessment method has contemporary consequences, such as making it simpler for educators to evaluate student progress.